Herança de resistência ao Meloidogyne incognita raça 2 em pepino - Salata, Ariane Cunha [UNESP]; Cardoso, Antonio Ismael Inácio [UNESP]; Wilcken, Sílvia Renata Siciliano [UNESP]; Bertolini, Erick Vinicius [UNESP] (Revista Brasileira de Ciencias Agrarias, 2015)
Root knot nematodes are among main problems in cucumber production, mainly in protected cultivation. The utilization of resistant cultivars is the most efficient and cheapest method of control. The objective of this research was to study the genetic inheritance of resistance to Meloidogyne incognita in cucumber. A cross between a inbred line obtained from Tsuyataro hybrid (L1), moderately resistant, and another from the Yoshinari hybrid (L2), susceptible to M. incognita race 2 was done. Population F1 (L1 x L2) between these two lines, generations F2 and F1BC1 were obtained for both lines (F1BC1L1 and F1BC1L2). Six treatments (two parental lines, generations F1, F2, F1BC1L1 and F1BC1L2) were evaluated in a complete block design with five replications. Plants were inoculated with the nematode (5,000 eggs per plant) after transplantation. At 60 days after inoculation gall and eggs mass index in root and reproduction factor (FR) were determined. Statistical-genetics analyses were performed according to the segregation obtained in generations F1, F2 and backcrossings to estimate the resistance of inheritance observed. The FR observed for line L2 (Yoshinari) was 7.21, more than twice of the observed for line L1 (Tsuyataro) that was 3.28. The partial resistance to M. incognita race 2 in 'Tsuyataro' cucumber is quantitative, with predominance of additive effects, with three main genes conditioning it.
Inheritance of resistance to Meloidogyne incognita race 2 in cucumber
Keywords: Cucumis sativus; Nematode; Reproduction factor; Root knot